Considerations of valvular heart disease in children with ventricular assist devices - Si, Ming-Sing; Sood, Vikram; Biniwale, Reshma; Peng, David (Frontiers in Cardiovascular Medicine, 2023)
Ventricular assist devices have become a valuable tool in the treatment of heart failure in children. The use of ventricular assist devices has decreased mortality in children with end-stage heart failure awaiting transplant. It is not uncommon for children with end-stage heart failure associated with cardiomyopathy or congenital heart disease to have significant systemic semilunar and atrioventricular valve regurgitation, which can impact the efficiency and efficacy of hemodynamic support provided by a ventricular assist device. Therefore, implanting clinicians should carefully assess for valve abnormalities that may need repair and impact device selection and cannulation strategy to effectively support this diverse population. The purpose of this review is to provide an overview of this important and relevant topic and to discuss strategies for managing these patients.